The effect of superoxide dismutase on protein exchange indicators in peritoneal exudate in the terminal phase of peritonitis - Karimova, Rana; Polukhova, Shahzada; Gasimova , Gulnara; Musayeva , Elnura; Baghirova, Leyla; Rustamova, Afag; Bakhshiyeva, Zenfira; Rustam-Zada, Aziza; Kazimova , Afag; Rustam-Zada, Azada; Abiyev, Huseyn (Acta Biomedica Atenei Parmensis, 2026)
Objective: The aim of the study was to investigate the changes in major indicators of protein metabolism in peritoneal exudate (PE) obtained from patients undergoing surgery in the terminal phase of peritonitis under the influence of the enzyme superoxide dismutase (SOD), and to determine the mechanisms of protein homeostasis disruption and the effect of neutralizing superoxide radicals on these processes during peritonitis. Methods: The study was conducted at the Scientific Research Center of Azerbaijan Medical University. Protein fractions in peritoneal exudate samples obtained from 30 (17 males and 13 females, aged between 34 and 72 years) patients were measured. Peritoneal exudate samples were divided into aliquots and analyzed with or without SOD after 6 and 24 hours. In samples incubated without SOD, time-dependent alterations in total protein and electrophoretic fractions were observed, indicating that oxidative processes alone can modify the protein profile of peritoneal exudates. SOD was added to the exudate samples and incubated at 10°C for 6 and 24 hours. Total protein, albumin, γ, α1, α2, and β globulins were determined. Results: In the terminal phase of peritonitis, the mean concentration of total protein in peritoneal exudate was 44±2.55 g/L, and albumin was 25±1.54 g/L. After the addition of SOD, total protein increased by 9.8% at 6 hours and by 27.3% at 24 hours, while albumin levels decreased by 26.7%. γ-globulin levels increased by 11.5% at 6 hours and even more at 24 hours. Simultaneously, decreases were observed in α1, α2, and β-globulin fractions. Conclusion: In the terminal phase of peritonitis, significant changes in the protein composition of peritoneal exudate were observed under the influence of SOD. These changes varied depending on the type of protein fraction and reflected the disturbances in protein metabolism and potential for correction.